A pronunciation program based on the suprasegmental features of phonology and its role in accent modification for esl adults ay udelas - Rodríguez Barría, Edwin Alexis (Panamá, Panamá : UDELAS, 2009)
Learning a new language requires more than time and patience.
ÍNDICE GENERAL Chapter One 1. Research problem 1.1 Statement of the problem 1.2 Justification 1.3 Objectives Cahpter two 2. Literature review 2.1 Operational key words related to the whole research 2.2 Historical groundwork Chapter three (Research method an design) Chapter four (results and findings) CONCLUSIONES RECOMENDACIONES BIBLIOGRAFÍA ANEXOS
Presentada para optar por el Título de Maestría en Docencia Superior
Contiene bibliografía
No se presta a domicilio
No se saca fotocopias
Keywords: PRONUNCIACIÓN -- TESIS DE MAESTRÍA; FONOLOGÍA -- TESIS DE MAESTRÍA; MAESTRÍA EN DOCENCIA SUPERIOR; UNIVERSIDAD ESPECIALIZADA DE LAS AMÉRICAS; UDELAS